Reversible intramolecular hydrogen transfer: a completely new mechanism for low impact sensitivity of energetic materials. Issue 5 (16th January 2019) - Xiong, Ying; Ma, Yu; He, Xudong; Xue, Xianggui; Zhang, Chaoyang
Abstract : The intramolecular H transfer of energetic NO2 -compounds has been recognized as a possible primary step in triggering molecular decomposition for a long time. Abstract : The intramolecular H transfer of energetic NO2 -compounds has been recognized as a possible primary step in triggering molecular decomposition for a long time. Nevertheless, studies on H transfer in different complex situations are limited, lacking a comprehensive understanding of its role in NO2 -compounds. In this work, twenty intramolecular H transfer reactions are studied for eighteen nitro compounds and compared with the NO2 partition in thermodynamics and kinetics. Three factors, including the high planarity of molecules, the short transfer distance between the target H and O atoms and the high protonation of the H atom are identified to facilitate H transfer. If H transfer is more kinetically favorable than NO2 partition, and if a reverse H transfer occurs with a barrier less than 30 kcal mol −1, we define it as a reversible one. In our study, for those impact insensitive nitro compounds with H50 larger than that of 2, 4, 6-trinitrotoluene, all of them are found to be accompanied with reversible H transfer, while the impact sensitive compounds are not. Accordingly, we propose that the reversible H transfer can effectively buffer the external stimuli against the molecular decomposition through chemical energy absorption/release. Beyond the conventional understanding that H transfer triggers molecular decomposition, this work builds a new correlation between reversible H transfer and the low impact sensitivity of energetic nitro-compounds.